Lesson study as a learning context in mathematics education - Ponte, João Pedro da (2019)
This chapter presents lesson study, a professional development process that originated in Japan, describing its main features with emphasis on how it may be regarded as a special form of teachers’ research on their own practice. We indicate some adaptations of lesson study to fit different purposes and pay attention to the participants’ experiences of collaboration, reflection and work in communities of practice. To illustrate these features, we present two case studies, one from Portugal and another from the UK.